2016
DOI: 10.1111/wvn.12136
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Neck Stretching Exercises Following Total Thyroidectomy on Reducing Neck Pain and Disability: A Randomized Controlled Trial

Abstract: Neck stretching exercises done immediately after a total thyroidectomy reduce short-term neck pain and disability symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 26 publications
1
30
3
Order By: Relevance
“…on the other hand, Jang et al [20] found that there was no significant difference determined between the stretching exercise group and the control one in terms of neck discomfort or RoM 3 months after thyroidectomy. The study results also disagree with Ayhan et al [18], who found no significant differences between the stretching neck exercises group and the control group with regard to neck pain and disability or neck sensitivity and pain with neck movements 1 month after total thyroidectomy.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…on the other hand, Jang et al [20] found that there was no significant difference determined between the stretching exercise group and the control one in terms of neck discomfort or RoM 3 months after thyroidectomy. The study results also disagree with Ayhan et al [18], who found no significant differences between the stretching neck exercises group and the control group with regard to neck pain and disability or neck sensitivity and pain with neck movements 1 month after total thyroidectomy.…”
Section: Discussioncontrasting
confidence: 99%
“…The outcomes are also in line with the observations presented by Ayhan et al [18], who investigated the effect of neck stretching exercises after total thyroidectomy on neck pain and disability and reported a statistically significant reduction in pain and disability. Abd-El Mohsen and Ahmed [19] revealed that applying neck stretching exercises significantly improved the neck condition concerning neck pain and disability 1 week after total thyroidectomy.…”
Section: Discussionsupporting
confidence: 91%
“…Finally, 17 manuscripts were selected and one of these was added from the bibliography because of its relevance. 1,[16][17][18][19][20] C Quéralt et al 1 Retrospective study N=200 -There were no deaths during follow-up -18 patients with postoperative hematoma, 17% were treated with anti coagulation compared to 13% of patients without.…”
Section: Resultsmentioning
confidence: 99%
“…The sample of subjects included in this study is representative of the general population undergoing thyroidectomy, with similar socio‐demographic characteristics (Ayhan et al, ; Takamura et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The sample of subjects included in this study is representative of the general population undergoing thyroidectomy, with similar socio-demographic characteristics (Ayhan et al, 2016;Takamura et al, 2005). Takamura et al (2005) observed neck pain symptoms in thyroidectomy patients, which continue for a long time after surgery and influence the daily life activities.…”
Section: Discussionmentioning
confidence: 99%